EXPLORING THE ASSOCIATION OF MEANING IN LIFE WITH PSYCHOLOGICAL DISTRESS IN MALE PATIENTS WITH SUBSTANCE USE DISORDER IN PAKISTAN - Khan, Muhammad Ali; Shahzad, Salman; Bano, Nasreen; Bano, Zakia; Siddiqui, Mahreen (Journal of Pakistan Psychiatric Society, 2022)
The objective of the present research is to explore the predictive association of meaning in life (presence & search) with psychological distress (depression, anxiety & stress) in people with substance use disorder. Sample of the present study comprised 200 Muslim participants (male patients with substance use disorder), ages ranging from 18 to 45 years (M =18; SD =6.55). The sample was recruited from different substance use treatment and rehabilitation centers situated in different areas of Karachi, through purposive sampling. Instruments used in this study were the Personal Information Form, Meaning in Life Questionnaire (MLQ; Stegaer, et al., 2006), and Depression Anxiety and Stress Scale (DASS; Lovibond, & Lovibond, 1995). Regression analysis shows a significant predictive relationship of meaning in life (i.e., presence & search of the meaning) with depression (adj R2=.988, F (2, 198) =8278.46, P < .0001(, anxiety (adj R2=.943, F (2, 198) =1659.82, P < .0001(, stress (adj R2=.982, F (2, 198) =5390.78, P < .0001(. Overall findings revealed that meaning in life is a significant predictor of psychological distress (i.e., depression, anxiety & stress) in people with SUD. The finding and implications are discussed in detail. Keywords: Meaning in life, presence, search, depression, anxiety, stress, substance use disorder